2017
DOI: 10.18632/oncotarget.18854
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of glycolysis and glutaminolysis as a therapeutic strategy in the treatment of ovarian cancer

Abstract: Cancer cell metabolism is required to support the biosynthetic demands of cell growth and cell division, and to maintain reduction oxidaton (redox) homeostasis. This study was designed to test the effects of glucose and glutamine on ovarian cancer cell growth and explore the inter-relationship between glycolysis and glutaminolysis. The SKOV3, IGROV-1 and Hey ovarian cancer cell lines were assayed for glucose, pyruvate and glutamine dependence by analyzing cytotoxicity, cell cycle progression, apoptosis and ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…A previous study showed that 2-dG impacted the cell viability of lymphoma cells as a single agent and reduced cell numbers synergistically with PI3K inhibitors and c-MYC antagonists [ 34 ]. Also, inhibition of glycolysis by 2-dG in ovarian cancer cell lines reduced cell proliferation [ 35 ]. Similarly, 2-dG as a single agent was used to selectively kill acute lymphoblastic leukemia cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that 2-dG impacted the cell viability of lymphoma cells as a single agent and reduced cell numbers synergistically with PI3K inhibitors and c-MYC antagonists [ 34 ]. Also, inhibition of glycolysis by 2-dG in ovarian cancer cell lines reduced cell proliferation [ 35 ]. Similarly, 2-dG as a single agent was used to selectively kill acute lymphoblastic leukemia cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to patients' individualities and tumors heterogeneity, variable response rates are often observed making the identification of more effective drugs very urgent [272,273]. In this regard, the concomitant inhibition of antioxidant circuits and metabolic pathways that support the redox balance of malignant cells, delineates a promising anti-cancer strategy [274][275][276][277][278][279][280][281][282][283]. It is known that most of the metabolic changes promoting cancer cells proliferation and tumor growth induce also an increased ROS generation, counterbalanced by an antioxidant response that prevents cell death [234,284,285].…”
Section: Strategies To Negatively Modulate Nrf2 Signaling/pathwaymentioning
confidence: 99%
“…These types of alterations in mitochondrial function specifically in cancer cells have raised prospects for therapeutic targeting of mitochondria in cancer cells. Notably, metabolic profiles defining OXPHOS vs glycolytic status for aGCT cells, as well as EOCs, have yet to be well- reported [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%